Adoption of renewable heating systems: An empirical test of the diffusion of innovation theory. (15th April 2017) - Franceschinis, Cristiano; Thiene, Mara; Scarpa, Riccardo; Rose, John; Moretto, Michele; Cavalli, Raffaele
Abstract: The implementation of heating technologies based on renewable resources is an important part of Italy's energy policy. Yet, despite efforts to promote the uptake of such technologies, their diffusion is still limited while heating systems based on fossil fuels are still predominant. Theory suggests that beliefs and attitudes of individual consumers play a crucial role in the diffusion of innovative products. However, empirical studies corroborating such observations are still thin on the ground. We use a Choice Experiment and a Latent Class-Random Parameter model to analyze preferences of households in the Veneto region (North-East Italy) for key features of ambient heating systems. We evaluate the coherence of the underlying preference structure using as criteria psychological constructs from the Theory of Diffusion of Innovation by Rogers. Our results broadly support this theory by providing evidence of segmentation of the population consistent with the individuals' propensity to adopt innovations. We found that preferences for heating systems and respondents' willingness to pay for their key features vary across segments. These results enabled us to generate maps that show how willingness to pay estimates vary across the region and can guide local policy design aimed at stimulating adoption of sustainable solutions. Highlights: We relate preferences for wood pellet heating systems to Diffusion of Innovation theory. We found a segmentation of the population according to individual innovativeness. Preferences for wood pellet heating systems vary across population segments. Public intervention seems necessary to foster adoption among late adopters.